Conceptual Framework for Assessing Sustainability of Urban Freight Transport. Issue 10 (2022) - Ayadi, Hana; Hamani, Nadia; Benaissa, Mounir; Kermad, Lyes
Abstract: Nowadays, improving the sustainability of urban freight transport is of paramount importance. The work aims to help freight transport actors in the evaluation of sustainability with a vision that considers the specificities of the city. Thus, we propose a conceptual approach to define sustainability dimensions that are not only the economic, the environmental and the social/societal dimensions, but also the political and spatial ones. They are of particular interest noteworthy so as to evaluate urban freight transport sustainability. We also introduce the concepts of weak, limited and strong sustainability. The proposed approach is used to construct adequate indicators for decision support in urban freight transport.